EXPLORING STUDENTS REASONING PATTERNS ON REPRODUCTIVE SYSTEM OF PLANTS AND ANIMALS MATERIAL - Anggraini, Widra Dwi; Pertiwi, Faninda Novika (Science Education, Institut Agama Islam Negeri Ponorogo, 2024)
The 21st century requires students to have high-level thinking abilities. One of the thinking abilities that students must have is logical reasoning. In learning, especially science, scientific logical thinking is very important. Science learning generally focuses on factual memory and experiments, so that both can improve students' scientific reasoning abilities. In the learning process in class, students have different reasoning patterns in understanding a problem. From this background, the aim of this research is to determine students' scientific logical reasoning patterns in solving problem-based problems that integrate material on plant and animal breeding systems and to determine teachers' strategies in efforts to improve students. 'logical thinking skills in scientific reasoning. This research was conducted at a junior high school in the city of Ponorogo with a sample of Ninth grade B students. The method used was a qualitative phenomenological approach. Data collection techniques use interviews, diagnostic test instruments and documentation. Based on the research results, the teacher's strategy in developing students' reasoning skills is to provide problem-based problems based on three indicators of logical thinking skills, namely thinking sequence, argumentation and inference skills. Meanwhile, students can use different reasoning patterns in solving problems given by the teacher. This research is new or new from previous research, namely the N-Vivo software is used for data analysis and is presented in depth with qualitative descriptions.